Cost-Effective Log Management Through Data Compression and Filtering - Aakash Aluwala (North American Journal of Engineering Research, 2021)
This paper aims at identifying a cost efficient approach to log management though data compression and filtration method. In doing so, the approach optimizes the system’s storage effectiveness and the timely access to data, thereby increasing the system’s efficiency as well as its security. The paper proves that storage cost is reduced and time for incident response is improved as the result of using effective log management in the current IT infrastructure.